PERCUTANEOUS ENDOSCOPIC GASTROSTOMY - M. I. Kuzmin-Krutetskiy; A. E. Demko; A. I. Safoev; A. E. Akkalaeva; L. I. Karimov (Вестник хирургии имени И.И. Грекова)
The percutaneous endoscopic gastrostomy takes an important place in operative endoscopy of the digestive system. At the same time it is the method of choice in patients who need a long-term administration of enteral feeding. Given article reflects the main indications, contraindications and complications of the percutaneous endoscopic gastrostomy and presents the basic stages of the method. The authors hope, that the data would be useful for both entry-lever surgeon-endoscopists and specialists who used the method.